2022
DOI: 10.1007/s11517-021-02466-z
|View full text |Cite
|
Sign up to set email alerts
|

Muscle force estimation from lower limb EMG signals using novel optimised machine learning techniques

Abstract: The main objective of this work is to establish a framework for processing and evaluating the lower limb electromyography (EMG) signals ready to be fed to a rehabilitation robot. We design and build a knee rehabilitation robot that works with surface EMG (sEMG) signals. In our device, the muscle forces are estimated from sEMG signals using several machine learning techniques, i.e. support vector machine (SVM), support vector regression (SVR) and random forest (RF). In order to improve the estimation accuracy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…We used sEMG to demonstrate the positive effects of yoga on balance, which was rare in previous studies. Previous studies showed that sEMG was able to accurately measure muscle activity through bioelectrical changes [50, 51, 52]. TA played an important role in the stabilization of OLS [53], and the stability of the sEMG signal amplitude during the process of maintaining balance meant the improvement of balance efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used sEMG to demonstrate the positive effects of yoga on balance, which was rare in previous studies. Previous studies showed that sEMG was able to accurately measure muscle activity through bioelectrical changes [50, 51, 52]. TA played an important role in the stabilization of OLS [53], and the stability of the sEMG signal amplitude during the process of maintaining balance meant the improvement of balance efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We used sEMG to demonstrate the positive effects of yoga on balance, which was rare in previous studies. Previous studies showed that sEMG was able to accurately measure muscle activity through bioelectrical changes [50,51,52].…”
Section: Effects Of Practicing Yoga As a Long-term Warm-up On Balancementioning
confidence: 99%
“…It could be that the number of involved muscles in the upper-limb dataset was less than that of the lower-limb dataset. Moreover, unlike black-box models such as ANN or SVM (Mokri et al, 2022), our method is a grey-box model, in which the model interpretation is possible (Figures 9,10). The activity of each muscle could be provided for each active muscle during recording to provide insights into load-sharing problems (Rojas-Martínez et al, 2019).…”
Section: The Grey-box Structurementioning
confidence: 99%
“…It was seen that different muscles responded differently to varying speeds of walking. Camila et al used kinematic and kinetic data as inputs to musculoskeletal model to simulate muscle activation for walking and running for lower limb [9]. Machine learning techniques were also implemented to predict force from EMG, along with IMU and load cells [10].…”
Section: Introductionmentioning
confidence: 99%